The introduction of the Africanised honey bee: A stinging menace or a blessing of the Americas? - Moreno Reategui, Jorge Antonio (2020)
In 1956, Brazilian scientist Warwick Estevam Kerr, introduced queens of the African honey bee (AHB) from South Africa to breed with European honey bees (EHB) in order to improve honey production in Brazil. Some of the AHB swarmed by accident out of the experimental apiary, located in Rio Claro-São Paulo State, and started to spread. Today, these have mixed with EHB and exist all over Brazil, the Neo tropic of South America, Central America, and South USA. This situation created drastic changes in the management of bees across the region.